Regulation of Natural Killer Cell Function by STAT3 - Cacalano, Nicholas A. (Frontiers in Immunology, 2016)
Natural killer (NK) cells, key members of a distinct hematopoietic lineage, innate lymphoid cells, are not only critical effectors that mediate cytotoxicity toward tumor and virally infected cells but also regulate inflammation, antigen presentation, and the adaptive immune response. It has been shown that NK cells can regulate the development and activation of many other components of the immune response, such as dendritic cells, which in turn, modulate the function of NK cells in multiple synergistic feed back loops driven by cell–cell contact, and the secretion of cytokines and chemokines that control effector function and migration of cells to sites of immune activation. The signal transducer and activator of transcription (STAT)-3 is involved in driving almost all of the pathways that control NK cytolytic activity as well as the reciprocal regulatory interactions between NK cells and other components of the immune system. In the context of tumor immunology, NK cells are a first line of defense that eliminates pre-cancerous and transformed cells early in the process of carcinogenesis, through a mechanism of “immune surveillance.” Even after tumors become established, NK cells are critical components of anticancer immunity: dysfunctional NK cells are often found in the peripheral blood of cancer patients, and the lack of NK cells in the tumor microenvironment often correlates to poor prognosis. The pathways and soluble factors activated in tumor-associated NK cells, cancer cells, and regulatory myeloid cells, which determine the outcome of cancer immunity, are all critically regulated by STAT3. Using the tumor microenvironment as a paradigm, we present here an overview of the research that has revealed fundamental mechanisms through which STAT3 regulates all aspects of NK cell biology, including NK development, activation, target cell killing, and fine tuning of the innate and adaptive immune responses.